DESCRIPTION AND POPULATION FLUCTUATION OF TEAK SKELETONIZER, EUTECTONA MACHAERALIS WALKER ON TEAK - N. R. CHAUHAN; M. G. PATEL; M. R. DABHI; D. M. KORAT; R. K. THUMAR (The Bioscan, 2012)
Studies on description, measurement and population fluctuation of teak skeletonizer, Eutectona machaeralis Walker revealed that the eggs of the pest were round in shape, greenish-white in colour and translucent. Diameter of the eggs was 0.27 + 0.04 mm. Average length and breadth of first, second, third, fourth and fifth instar larvae were 2.08 ± 0.23, 7.50 ± 1.11, 11.61 ± 1.68, 17.63 ± 1.81, 23.42 ± 1.06 and 0.26 ± 0.03, 0.97 ± 0.14, 1.30 ± 0.27, 1.72 ± 0.30, 2.14 ± 0.17, respectively. The corresponding values of head width were 0.21 ± 0.04, 0.80 ± 0.11, 1.11 + 0.18, 1.51 ± 0.29 and 1.66 ± 0.36 mm, respectively. Average length and breadth of pre-pupae was an 16.59 ± 2.73 and 2.85 ± 0.84 mm, respectively. Length and breadth of male pupae ranged from 10.00 to 13.00 and 2.20 to 3.20 mm, while in female, it ranged from 13.00 to 15.00 and 3.00 to 4.00 mm, respectively. Abdomen of female was wider than male, but it tapered posteriorly in both the sexes. Average length of female (from head to tip of abdomen) was 11.35 ± 0.97 mm, whereas, the breadth across the expanded wings was 23.11 ± 2.02 mm. The corresponding values for male was 10.14 ± 0.43 and 21.04 ± 1.09 mm, respectively. Activity of E. machaeralis commenced from the fifth week of May during 2006 and 2007 which reached to its peak in fourth week of July during 2006 and first week of August during 2007. Thereafter, it decreased up to first week of November during 2006 and 2007.